Building respirable powder architectures: utilizing polysaccharides for precise control of particle morphology for enhanced pulmonary drug delivery - Kadota, Kazunori; Uchiyama, Hiromasa; Kämäräinen, Tero; Tanaka, Shunsuke; Tozuka, Yuichi (Expert Opinion on Drug Delivery, 2024)
Introduction Dry powder inhaler (DPI) formulations are gaining attention as universal formulations with applications in a diverse range of drug formulations. The practical application of DPIs to pulmonary drugs requires enhancing their delivery efficiency to the target sites for various treatment modalities. Previous reviews have not explored the relation between particle morphology and delivery to different pulmonary regions. This review introduces new approaches to improve targeted DPI delivery using novel particle design such as supraparticles and metal-organic frameworks based on cyclodextrin. Areas covered This review focuses on the design of DPI formulations using polysaccharides, promising excipients not yet approved by regulatory agencies. These excipients can be used to design various particle morphologies by controlling their physicochemical properties and manufacturing methods. Expert opinion Challenges associated with DPI formulations include poor access to the lungs and low delivery efficiency to target sites in the lung. The restricted applicability of typical excipients contributes to their limited use. However, new formulations based on polysaccharides are expected to establish a technological foundation for the development of DPIs capable of delivering modalities specific to different lung target sites, thereby enhancing drug deliver
Keywords: Polysaccharides; supraparticles; cyclodextrin-based metal-organic frameworks; morphology; particle engineering; dry powder inhaler